Treatment pathways in Finnish patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH) - Markku Pentikäinen; Piia Simonen; Pauliina Leskelä; Terttu Harju; Pertti Jääskeläinen; Christian Asseburg; Minna Oksanen; Erkki Soini; Christina Wennerström; Airi Puhakka; the FINPAH study group (Pulmonary Circulation)
Abstract Treatment patterns of pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) in Finland are unknown. Guidelines now recommend early escalation of treatment for PAH. We evaluated how well Finnish practice follows guidelines, and how treatment initiations and outcomes are related. The pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension patients in Finland cohort includes all PAH and CTEPH patients diagnosed between 2008 and 2020 in all Finnish university hospitals. Drug therapy was analysed in patients with medical/procedural history available, and changes in the 4‐tier comparative, prospective registry of newly initiated therapies for pulmonary hypertension (COMPERA) 2.0 risk score were evaluated. PAH patients (n = 268) were initially treated with monotherapy (52%) or double therapy (24%). After year 2015, double therapy use increased to 39%. PAH treatment at 1 year after diagnosis included phosphodiesterase 5 inhibitors (71%), endothelin‐receptor antagonist (48%), prostacyclin analogue (7%), calcium channel blocker (12%) and selexipag (1%). 35% achieved low risk at 1 year, increasing to 44% for patients diagnosed after 2015. Those remaining at intermediate‐high (IH) or high risk (H) (28%) were not treated less aggressively than others but were older, had more comorbidities, and often history of smoking. CTEPH patients (n = 189) were treated with pulmonary endarterectomy (PEA) (27%), balloon pulmonary angioplasty (BPA) (11%) and medical therapy only (41%) within 1 year from diagnosis. 45% achieved low risk at 1 year. We present additional results on treatment of IH and H patients, patient characteristics preceding death, and treatment persistence. We found less treatment of PAH patients with double or triple therapies and of CTEPH patients with PEA and BPA than expected but with good results. Patients not reaching low or intermediate COMPERA 2.0 were old and had comorbidities.